Pemanfaatan Tanaman Obat Keluarga (Toga) Di Kampung Iklim Rw 03 Kelurahan Tabek Gadang - Fathul Jannah; Ira Oktaviani RZ; Masnun; Alexsander Yandra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Changes in extreme weather or climate can cause various kinds of diseases such as flu, cough, diarrhea, dengue fever, and others. Family medicinal plants (TOGA) can be used to improve health, treat and prevent disease, and increase body resistance as immunomodulators. The Utilization of family medicinal plants can be an alternative treatment that is easy to obtain and increase family independence in improving their health status. RW 03 Tabek Gadang Village is one of the climate villages that focuses on implementing efforts to increase adaptation to climate change such as health problems that arise due to climate change. The purpose of this activity is to increase understanding related to TOGA to support the climate village program. Activities carried out in the form of planting TOGA, education about TOGA, and the practice of processing TOGA into traditional medicinal drinks. In TOGA planting, there were 16 types of plants planted on unused land in RW 03. There was an increase in knowledge after being given education about TOGA from 61.47 to 88.53 and participants were enthusiastic during the implementation of TOGA processing practices.